Context-Aware for Natural Language Processing Services using Microservices Architecture - Abdullah Aziz Sembada; Dhomas Hatta Fudholi; Raden Teduh Dirgahayu (Budapest International Research and Critics University, 2022)
The development of the industrial era 4.0 and big data has made Natural Language Processing much needed, especially when preprocessing data. With the Natural Language Processing service in order to make it easier for researchers to conduct research because some of their needs have been provided. Before providing services Natural Language Processing first does the system design. The system is built using a microservice architecture, microservice was chosen because it has the characteristics of being flexible, safe, isolated errors, making it very easy to develop the system.feature is added Context-Aware to make it easier for users to process data. The purpose of the research is to be able to integrate Context-Aware into the Natural Language Processing service system so that the system is able to provide recommendations for the most suitable algorithms from the data owned by the user. System test results show that Natural Language Processing service can shorten research on natural language processing. These results cannot be separated from the context-awareness that can determine the type of file or data inputted by the user, thus the user is directly directed by the system to process the file or data using a clustering or classification. The implementation of microservices is also very helpful in development, especially service or algorithms that will not interfere services with existing.